The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1991
DOI: 10.1002/jsfa.2740550102
|View full text |Cite
|
Sign up to set email alerts
|

Response of tea quality parameters to time of year and nitrogen fertiliser

Abstract: A B S T R A C T Though tea production continues throughout the year in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Mudau et al (2005) reported that the highest total polyphenol concentrations in bush tea occurred when P was applied at 300 kg ha -1 . The theaflavins and thearubigins contents in green tea varied with time of the year with application of 150 kg ha -1 P being the optimum (Owuor et al, 1991). Other quality parameters such as caffeine (Owuor et al, 1991) and free amino acid content (Ruan et al, 1998) in green, oolong and black tea responded positively to P application of 150 kg ha -1 .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Mudau et al (2005) reported that the highest total polyphenol concentrations in bush tea occurred when P was applied at 300 kg ha -1 . The theaflavins and thearubigins contents in green tea varied with time of the year with application of 150 kg ha -1 P being the optimum (Owuor et al, 1991). Other quality parameters such as caffeine (Owuor et al, 1991) and free amino acid content (Ruan et al, 1998) in green, oolong and black tea responded positively to P application of 150 kg ha -1 .…”
Section: Resultsmentioning
confidence: 98%
“…The theaflavins and thearubigins contents in green tea varied with time of the year with application of 150 kg ha -1 P being the optimum (Owuor et al, 1991). Other quality parameters such as caffeine (Owuor et al, 1991) and free amino acid content (Ruan et al, 1998) in green, oolong and black tea responded positively to P application of 150 kg ha -1 . Kamau et al (1999) reported that the levels of thearubigins and volatile flavour index were generally high when P was applied at 250 kg ha -1 .…”
Section: Resultsmentioning
confidence: 98%
“…Current research has shown that yields and quality can be improved with fertilization (Mudau et al, 2005(Mudau et al, , 2007, pruning, and application of growth regulators (Maudu et al, 2013). Among these agronomic practices, application of N, P, and K fertilizers was reported to have a pronounced effect on leaf total polyphenol content in Camellia sinensis (Owuor et al, 1991(Owuor et al, , 2000 and in bush tea (Mudau et al, 2005(Mudau et al, , 2007.…”
mentioning
confidence: 99%